Multifunctional Oval Shape Gold Nanoparticle Based Selective Detection of Breast Cancer Cells Using Simple Colorimetric and Highly Sensitive Two-Photon Scattering Assay - Lu, Wentong (2010)
Breast cancer is the most common cancer among women and it is the second leading cause of cancer deaths in women today. The key to the effective and ultimately successful treatment of diseases such as cancer is an early and accurate diagnosis. Driven by the need, in this article, we report for the first time a simple colorimetric and highly sensitive two-photon scattering assay for highly selective and sensitive detection of breast cancer SK-BR-3 cell lines in 100-cells/ml level using multifunctional (monoclonal anti-HER2/c-erb-2 antibody and S6 RNA aptamers conjugated) oval shape gold nanoparticle based nanoconjugate. When multifunctional oval shape gold nanoparticles were mixed with breast cancer SK-BR-3 cell line, a distinct color change occurs and two-photon scattering intensity increases by about 13 times. Experimental data with HaCaT non-cancerous cell line, as well as with MDA-MB-231 breast cancer cell line clearly demonstrated that our assay was highly sensitive to SK-BR-3 and it was able to distinguish from other breast cancer cell line which expresses low levels of HER-2. The mechanism of selectivity and assay’s response change, have been discussed. Our experimental results reported here open up a new possibility of rapid, easy and reliable diagnosis of cancer cell lines by monitoring the colorimetric change and measuring TPS intensity from multifunctional gold nanosystems.